Ancient DNA identification of domestic animals used for leather objects in Central Asia during the Bronze Age. (October 2016) - Schröder, Oskar; Wagner, Mayke; Wutke, Saskia; Zhang, Yong; Ma, Yingxia; Xu, Dongliang; Goslar, Tomasz; Neef, Reinder; Tarasov, Pavel E; Ludwig, Arne
The arid climate of many regions within Central Asia often leads to excellent archaeological preservation, especially in sealed funerary contexts, allowing for ancient DNA analyses. While geneticists have looked at human remains, clothes, tools, and other burial objects are often neglected. In this paper, we present the results of an ancient DNA study on Bronze Age leather objects excavated from tombs of the Wupu cemetery in the Hami Oasis and Yanghai cemetery in the Turpan Oasis, both in Xinjiang Uyghur Autonomous Region of northwestern China. In addition to species identification of goat ( Capra aegagrus/hircus ), sheep ( Ovis orientalis/aries ), and cattle ( Bos primigenius/taurus ), mitochondrial haplogroups were determined for several samples. Our results show that Bronze Age domesticated goats and sheep from the Hami and Turpan oases possessed identical or closely related haplotypes to modern domestic animals of this area. The absence of leather produced from wild animals emphasizes the importance of animal husbandry in the cultures of Wupu and Yanghai.